Deviation of cup alignment from target angle during press-fit insertion. Issue 1 (1st January 2018) - Suksathien, Yingyong; Sueajui, Jithayut; Piyapromdee, Urawit
Abstract: Background: Several factors lead to cup malalignment including preoperative pelvic tilt, inaccurate pelvic position on the operating table, pelvic movement during the operation and alignment change after screw fixation of the cup. There are few studies about the deviation of cup alignment from target angle during press-fit insertion, which may be the other cause of cup malalignment. The purpose of this study was to evaluate the deviation of cup alignment from target angle during press-fit insertion by using imageless navigation and to define any influential factors, including gender, age and side of operation. Methods: Between February 2016 and March 2017, patients undergoing total hip arthroplasty (THA) with imageless navigation were included in the present single-center study. Cup inclination angle was set at 40 degrees in all cases but the anteversion angle varied depending on the stem anteversion in each case using a combined anteversion technique. The final cup was aligned at target angles in both inclination and anteversion, the tracker was detached from the insertion handle and the surgeon inserted the cup until it was seated completely. The tracker was attached again to display both inclination and anteversion angles and these angles were recorded. Deviated Inclination Angles (DIA) and Deviated Anteversion Angles (DAA) in each case were calculated. Results: There were 124 cases in the present study. The mean age of the patients was 60.2 years (25–93). There were equal numbers of right-sided and left-sided operations, 62 cases each. There were 114 cases (91.9%) with DIA. The mean DIA was 2.65 ° (0 ° –8 °, SD 1.66). The DIA decreased in 107 cases (86.3%) with 12 cases (9.7%) showing a decrease of 5 ° or more. The DIA increased in 7 cases (5.6%) with 2 cases (1.6%) showing an increase of 5 ° or more. There were 103 cases (83.1%) with DAA. The mean DAA was 2.3 ° (0 ° –14 °, SD 2.3). The DAA increased in 78 cases (62.9%) with 11 cases (8.3%) increasing by 5 ° or more. The DAA decreased in 25 cases (20.2%) with 4 cases (3.2%) decreasing by 5 ° or more. The DIA was significantly higher in males than in females ( p = .012). There was significant correlation between DAA and patient's age ( p = .037). There was no significant difference between DIA or DAA and side of operation. Conclusion: Changes in cup orientation were observed in most cases during cup insertion with hammer blows detected by imageless navigation. Deviation of cup alignment from target angle during press-fit insertion was a possible cause of cup malalignment, male gender and patient's age were influential factors.